Effects of an artificially carbonated bath on athletic warm-up - Akamine, T.; Taguchi, N. (Journal of Human Ergology, 1998)
The effects of an artificially carbonated bath (36 degrees C, CO2 300 ppm, 20 minutes) on the warm-up of swimmers was compared with those of a freshwater bath (36 degrees C, 20 minutes). Carbon dioxide is reported to have a vasodilatory effect on peripheral blood vessels of cutaneous and muscular tissue and to promote blood flow. We observed that the warm-up effects of a carbonated bath before swimming on the hematocrit, white blood cell, total plasma protein, and total cholesterol levels in venous blood were significantly increased more than those of a freshwater bath before swimming in recovery period (p < 0.05). Thus the carbonated bath tended to be more effective for increasing the concentrations of blood components. In the recovery period, the carbonated bath before swimming also resulted in significantly smaller changes in blood lactic acid and heart rate than those of a freshwater bath before swimming (p < 0.05). The decrease in electromyography of the M. rectus femoris during swimming suggested more efficient muscle activity after a carbonated bath. Therefore after a carbonated bath, swimmers should have a higher reserve left in the cardiovascular system, resulting in better performance during swimming and less accumulation of fatigue-related metabolites after swimming.